Engaging primary healthcare nurses in men's health education: A pilot study. (March 2016) - Rizio, Taletha A.; Thomas, Wendy J.; O'Brien, Anthony Paul; Collins, Veronica; Holden, Carol A.; ,
Abstract: Many countries have identified a need for targeted men's health promotion within primary health care as part of broader men's health policy. Primary health care nurses are well placed to deliver such services but may lack the requisite skills. The aim of this study was to pilot the delivery phase of an education program and evaluate a train-the-trainer approach for delivering men's health education to primary health care nurses. The 8-h train-the-trainer workshop was designed to equip nurses to deliver men's health education workshops to peers. Surveys of facilitators (n = 18) and peer workshop participants (n = 98) evaluated their level of confidence in men's health and knowledge and skills in men's health promotion. After completing the train-the-trainer workshop, most facilitators expressed confidence (92%), and all indicated sufficient knowledge and access to resources to deliver a peer workshop. All agreed that the module was sufficiently flexible to suit their local setting. Following the peer education workshop, facilitators and workshop participants reported high levels of confidence and knowledge in men's health promotion. This pilot evaluation suggests train-the-trainer is an effective model to deliver men's health education across a range of settings, with a flexible approach to raising awareness and improving the skills of primary health care nurses in men's health promotion. Highlights: Primary health care nurses are well placed to deliver targeted men's health promotion. A train-the-trainer approach for men's health education for nurses was evaluated. After training, most facilitators expressed confidence in delivering a peer workshop. After peer workshops participants felt confident and knowledgeable about men's health. Train-the-trainer appears to be an effective model to deliver men's health education.